2001
DOI: 10.1063/1.1387256
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectroscopy on individual CdSe/ZnMnSe quantum dots

Abstract: Optical single dot studies in wide-band gap diluted magnetic CdSe/ZnMnSe quantum dots have been performed. Due to the sample design, the photoluminescence energy of the quantum dot signal is energetically below the internal Mn2+ transition, resulting in high quantum efficiencies comparable to nonmagnetic CdSe/ZnSe quantum dots. Magnetic-field- and temperature-dependent measurements on individual dots clearly demonstrate the exchange interaction between single excitons and individual Mn2+ ions, resulting in a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…This is similar to the results by Titova et al [25] where pronounced PL peaks at approximately 2.1 eV were observed for samples grown by a MBE growth procedure where 0.2 to 0.5 monolayers of MnSe were deposited on ZnSe buffer layers prior to the deposition of the CdSe layer from which nominally pure CdSe QDs formed after the deposition of a ZnSe capping layer [6,7]. None of the above mentioned studies [23][24][25] confirmed their PL peak assignments with structural analyses on the same samples. Since we indeed observed (110) superlattice spots in SAED patterns of [001] plan views prepared from the samples presented in ref.…”
Section: A Ii-vi Quantum Dotssupporting
confidence: 77%
See 3 more Smart Citations
“…This is similar to the results by Titova et al [25] where pronounced PL peaks at approximately 2.1 eV were observed for samples grown by a MBE growth procedure where 0.2 to 0.5 monolayers of MnSe were deposited on ZnSe buffer layers prior to the deposition of the CdSe layer from which nominally pure CdSe QDs formed after the deposition of a ZnSe capping layer [6,7]. None of the above mentioned studies [23][24][25] confirmed their PL peak assignments with structural analyses on the same samples. Since we indeed observed (110) superlattice spots in SAED patterns of [001] plan views prepared from the samples presented in ref.…”
Section: A Ii-vi Quantum Dotssupporting
confidence: 77%
“…For the lack of contradicting structural analysis results, we speculate that our tentative assignment of the peaks at approximately 2 eV and 2.1 eV to atomically ordered agglomerates and atomically ordered QDs might also be applicable to the related peaks around 2.1 eV that Kim et al [2 3] and Bacher at al. [24] observed.…”
Section: A Ii-vi Quantum Dotsmentioning
confidence: 94%
See 2 more Smart Citations
“…In order to achieve a good control of the magnetic properties, it is of great importance to control the number and position of magnetic ions inside of the dots. There were several papers reporting properties of QDs with large number of Mn ions, typically of the order of 100, confined in the QDs [2][3][4], and more recently with only one single Mn ion [1]. In this paper we present a method to introduce only a small number of Mn ions, in the order of 10, directly into the QDs and we believe to place most of them in the centre of our QDs.…”
Section: Introductionmentioning
confidence: 93%